Peruvian auteur cinema in globalization era: between transgression and marginalization - Rivas Frías, Bruno (2020)
The genre of Peruvian auteur cinema has been characterized by representing the country’s social problems by representing speeches that are positioned as an alternative to hegemony. This article presents how, even during the period of greatest economic growth of Peru, this genre has maintained the tradition of being an alternative voice by stating that the country’s entry into the globalized economy has not solved the social problems of much of the population. To accomplish that, the films Chicha tu madre, El premio, Paraíso and El evangelio de la carne were analyzed. These films have in common to tell stories set in marginal settings and in which their protagonists must resort to transgression in order to survive. The characters that representing the sinlugar, those individuals who are prevented from participating in the benefits of the informative and economic exchanges that promised the entry of Peru to the globalized market.